Diagnosis and treatment of communicating bronchopulmonary foregut malformation: Report of two cases and review of the literature. Issue 11 (March 2017) - Ren, Hongxia; Duan, Liqiong; Zhao, Baohong; Wu, Xiaoxia; Zhang, Hongyi; Liu, Caixia
Abstract: Rationale: Communicating bronchopulmonary foregut malformation (CBPFM) is a rare congenital malformation involving both the digestive and respiratory systems. To our best knowledge, most cases of CBPFM reported in the literature were in infancy or adulthood and CBPFM in infantile is even rarer with a high case-fatality rate partly due to misdiagnosis. Patient concerns: We presented 2 cases of neonatal CBPFM. A 11-hour male newborn was admitted because of moaning for 7 hours, and a 1-day male newborn was referred to us with profuse foams, choking on breast-milk feeding and facial cyanosis. Diagnoses: With the assistance of upper gastrointestinal tract imaging and contrast-enhanced chest computed tomography (CT), the diagnosis was established according to the most recent diagnostic criteria. Interventions: The case one recieved a lower left pneumonectomy and surgical repair of esophageal fistula. The case two was performed with a surgical repair of esophageal atresia and esophageal tracheal fistula firstly, and then also received a repair of communicating bronchopulmonary foregut malformation two weeks after the first operation. Outcomes: The case one was cured and discharged 2 weeks after admission. Unfortunately the case two died from respiratory failure. Lessons: Pediatric surgeons should therefore be aware that type I CBPMF is rare and preoperative diagnosis is usually difficult. Maldiagnosis is uncommon because clinicians often focus their attention on esophageal atresia and neglect pulmonary abnormalities. Other than upper gastrointestinal tract radiography and CT scan, bronchoscopy should be considered in pediatric patients with esophageal atresia complicated with pulmonary abnormalities, knowing that bronchoscopy may help confirm the diagnosis and select surgical strategies.